The role of peroxisome proliferator-activated receptor in the treatment of non-alcoholic fatty liver disease - Sun Xin; Zhang Yan; Xie Meilin (Acta Pharmaceutica)
Non-alcoholic fatty liver disease (NAFLD) has been defined as a spectrum of histological abnormalities and is characterized by significant and excessive accumulation of triglycerides in the hepatocytes in patients without alcohol consumption or other diseases. Current studies are targeting new molecular mechanisms that underlie NAFLD and associated metabolic disorders. Many therapeutic targets have been found and used in clinical studies. Peroxisome proliferator-activated receptors (PPARs) are among the potential targets and have been demonstrated to exert a pivotal role in modulation of NAFLD. Many drugs developed so far are targeted at PPARs. Thus, the aim of this paper is to summarize the roles of PPARs in the treatment of NAFLD.